Militância, organização e mobilização antiproibicionista da maconha: coletivos, eventos e marchas em Natal (RN) - Campos, Natália de (2013)
Based on the proposal entitled anti-prohibitionist, contrary to prohibition and illegality of cannabis and its use, the anti-prohibitionist Collectives proposes to discuss the topic of drugs, especially marijuana, aiming decriminalization and legalization of this psychoactive. With this idea was articulated anti-prohibitionist movement in Natal, by organizing collectives that discuss issues related to drug use and conduct activities directed to this issue, such as Marijuana Marches and Cycles of Debates anti-prohibitionist. In this study we sought to understand the positioning in social and cultural terms, the marijuana users participating of the collectives, on the situation of illegality of their actions, in front of social, legal and moral question involved in the illicit psychoactive, through initiatives conferences, events and demonstrations for this purpose